Cladorchis pyriformis (Diesing, 1838) (digenea, cladorchiidae): New rodent host and geographic records in Argentina - Guerreiro Martins, Natalia Beatriz (2019)
This work contributes to the knowledge of digeneans in two species of Holochilus Brant, 1835 from nine localities of Argentina. Morphological characteristics and ecological data are provided. Holochilus vulpinus (Brants, 1827) and H. chacarius Thomas, 1906 were parasitized by only one digenean species, Cladorchis pyriformis (Diesing, 1838). The morphometric features of this species and those reported by previous authors from South America are presented and compared. Holochilus vulpinus and a locality of Corrientes province was the host most frequently parasitized. Cladorchis pyriformis is recorded for the first time in H. chacarius.